3D Electric Power Demand Forecasting as a Tool for Planning Electrical Power Firm's Activity by Means of Geostatistical Methods - Namysłowska-Wilczyńska, Barbara; Wilczyński, Artur (Prognozowanie (3D) zapotrzebowania na moc elektryczną jako narzędzie w planowaniu działalności firmy energetycznej z zastosowaniem metod geostatystycznych, 2010)
Geostatistical methods were applied to forecasting area - time (3D) electrical power demand. Spatial analyses based on node load data for two kinds of electrical power networks, i.e. the 220/400 kV network covering the whole area of Poland and the 110 kV network for a selected subarea of Poland, were carried out. The 20-year power variation structure for the two kinds of networks was analyzed using the directional variogram function. Power demand forecasts for 1 year and 5 years were made using ordinary block kriging. The results of the power estimation and forecasting of averages Z* and the estimation standard deviation ok show that the employed techniques are useful and effective. Therefore they arc recommended for use by power firms.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 95-112
Keywords: geostatistical (3D) modelling; area – time forecasting; electrical loads; directional variogram; ordinary kriging